Numerical Simulation of the Locality of Erosional Damages by Storm Waves in Searching for Measures to Conserve Bonggil Beach, Korea - Do, Jong Dae; Jin, Jae-Youll; Lee, Byunggil; Jeong, Weon Mu; Choi, Jin Yong; Hyun, Sang Kwon; Kim, Kihyun; Chang, Yeon S. (Frontiers in Marine Science, 2022)
Coastal erosion caused by extreme storms can reduce the value of beaches. Under the scenario of climate change, the storm intensity may increase and the resulting severe erosion can lead to disastrous damages on the beaches. Therefore, it is crucial to find appropriate measures and adaptation plans to conserve the beach from storm attacks. In this study, numerical models were applied to analyze the dune erosion in Boggil Beach, Korea, occurred by Typhoon Tapah in September 2019. Two models were used as Telemac-2D was run in larger domains for producing forcing conditions. XBeach was then applied to simulate the 2019 dune erosion after validation using observational data from a post-event field experiment performed in 2020. The model results showed reasonable agreement with the observational data except for the overestimation of erosion that was likely caused by characteristic pattern of sediment that was a mixture of sand and gravel and the accuracy of model results decreased due to the existence of gravel. The results also confirmed the locality of erosional damage by which the dune erosion was severest in the southern part of the beach. This locality was caused because the water depth was steeper in this area, which kept the wave energy in this area higher than that in the northern part. The uneven distribution of depth was induced by natural and anthropogenic causes. Three cases of model tests were performed to determine an appropriate measure to preserve the beach from future storm attacks – two were to place a submerged breakwater (SB), and one to place a submerged groin(SG). Although the SBs could directly protect the shore from erosion in the lee of the SBs, they could cause additional erosions at unexpected seabed areas. Although the SG was not the best in protecting the beach from the dune erosion, it could minimize the side effect. This measure was also environmentally friendly by keeping the sediments within the coastal cell around the SG so that the beach maintenance could be feasible through replenishment. In addition, the SG could also save the initial cost by reducing its size, and would be more effective, if the recovery process considered, because the SBs would disturb the onshore sediment motions under milder wave conditions. The results of this study can be applied for decision-making to establish future adaptation plans from storm impacts in Bonggil Beach.